Diet-Induced Obesity Promotes Liver Metastasis of Pancreatic Ductal Adenocarcinoma via CX3CL1/CX3CR1 Axis. (18th April 2022) - Sun, Yue; Zhang, Xiao-Xin; Huang, Shan; Pan, Hong; Gai, Yan-Zhi; Zhou, Yao-Qi; Zhu, Lei; Nie, Hui-Zhen; Li, Dong-Xue
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive cancers, and the patients are generally diagnosed with distant metastasis. Liver is one of the preferred organs of distant metastasis, and liver metastasis is the leading cause of death in PDAC. Diet-induced obesity (DIO) is a risk factor for PDAC, and it remains unclear whether and how DIO contributes to liver metastasis of PDAC. In our study, we found that DIO significantly promoted PDAC liver metastasis compared with normal diet (ND) in intrasplenic injection mouse model. RNA-seq analysis for liver metastasis nodules showed that the various chemokines and several chemokine receptors were altered between ND and DIO samples. The expression levels of CX3CL1 and CX3CR1 were significantly upregulated in DIO-induced liver metastasis of PDAC compared to ND. Increased CX3CL1 promoted the recruitment of CX3CR1-expressing pancreatic tumor cells. Taken together, our data demonstrated that DIO promoted PDAC liver metastasis via CX3CL1/CX3CR1 axis.